Neutrality of State Civil Apparatus in General Elections in Indonesia - Bagus Sarnawa; Muhammad Haris Aulawi (International Journal of Science and Environment (IJSE), 2026)
This research aims to provide an academic manuscript on the model of the neutrality of the State Civil Apparatus in the personnel system in Indonesia. Therefore, this research departs from the formulation of the problem: What is the model of the neutrality of the State Civil Apparatus in General Elections in Indonesia. To answer the formulation of the maslaah, this study will use secondary data. Namely data obtained from literature studies through primary, secondary and tertiary legal materials. To explore the secondary data, the researcher will conduct field research by conducting interviews with resource persons, namely the Head of the State Civil Service, the Chairman of the General Election Supervisory Agency and Regional Heads. The results of the study show that the neutrality of the State Civil Apparatus has never been realized since the independence period until the present time, this has happened as a result of the intervention of political officials against the State Civil Apparatus. Therefore, the effort as well as the realization of the model of net neutrality of the State Civil Apparatus in general elections is by separating political positions and kearier positions.